Bioecological Properties and Growing Technology of Capsella Bursa-Pastoris L. In Uzbekistan (IN THE CONDITIONS OF SYRDARYA REGION) - Farrukh Abdukholikov; Abrorbek Eshtemirov; Ma’sud Norkulov (American Journal of Botany and Bioengineering, 2025)
This article is devoted to the bioecological properties and cultivation technology of the medicinal plant - Capsella bursa-pastoris. In order to determine the bioecological properties of the plant, its morphological indicators were determined in laboratory and field conditions. The chemical composition was analyzed and medicinal properties were studied. Cultivation technology was improved and yield indicators were calculated.